Guiding Questions for Choosing the Right Tools to Measure Early Childhood Outcomes : Why, What, Who, and How - Pushparatnam, Adelle; Seiden, Jonathan Michael; Luna Bazaldua, Diego Armando (Washington, DC: World Bank, 2022)
A growing understanding of the importance of children’s earliest years has led to an increasing desire to measure early childhood development (ECD) outcomes. There are now nearly 150 tools for measuring ECD outcomes internationally, which can make it challenging to choose an appropriate measurement tool for a given measurement effort. This document guides the user through the why, who, what, and how questions that must be considered prior to selecting tools for measuring ECD outcomes. Users should document their responses at each step to collate the information needed to identify and select an appropriate ECD measurement tool.